Excel hacks - Hawley, David E. (Hacks series., 2004)
If you think that getting creative with Excel means the underhanded tweaking of numbers, think again. Excel Hacks shows even the most experienced users how to do things with Excel they might never have thought of doing--and lets them have a little fun while they're at it. Microsoft Excel is not just the dominant spreadsheet in the world; it's also one of the most popular applications ever created. Its success lies not only in its power and flexibility, but also in its streamlined, familiar interface that casually conceals its considerable capabilities. You don't need to know everything that Excel can do in order to use it effectively, but if you're like the millions of Excel power users looking to improve productivity, then Excel Hacks will show you a wide variety of Excel tasks you can put to use, most of which are off the beaten path. With this book, Excel power users can bring a hacker's creative approach to both common and uncommon Excel topics--"hackers" in this sense being those who like to tinker with technology to improve it. The "100 Industrial Strength Tips and Tools" in Excel Hacks include little known "backdoor" adjustments for everything from reducing workbook and worksheet frustration to hacking built-in features such as pivot tables, charts, formulas and functions, and even the macro language. This resourceful roll-up-your-sleeves guide is for intermediate to advanced Excel users eager to explore new ways to make Excel do things--from data analysis to worksheet management to import/export--that you never thought possible. Excel Hacks will help you increase productivity with Excel and give you hours of "hacking" enjoyment along the way